Consortium management of digital content in the BUCOC Network - Martín, Sandra Gisela; Lago, María Soledad (Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2021)
The Network of Catholic Universities and Catholic Orientation of Argentina (UC-OC Network) is presented and within its framework the objectives, services and organizational structure of the BUCOC library network. The Strategic Plan 2021-2022 stands out with its vision, mission and objectives and focuses on the strategic line on the consortium management of digital content. A brief tour is made on the management models of the electronic book: business model, acquisition model and access model and then the different sources of content acquisition, the access modalities and the technologies used are discussed. Problems in the management of digital content are approached from two perspectives: in relation to publishers and from the point of view of libraries, confronting the publishers sales model versus the library purchasing model. Finally, the consortium management model of digital content in the BUCOC Network is presented and the achievements and challenges of cooperative work are highlighted.